Edukasi Cara Bermedia Sosial dan Pencegahan Konten Internet Negatif bagi Masyarakat Kelurahan Polaman - Deden Istiawan; Khoirul Anam Dahlan (Lembaga Pengembangan Kinerja Dosen, 2026)
Rapid development of information and communication technology has significantly increased use of the internet and social media across various segments of society. However, adoption grew of digital technology accompanied by numerous risks, included spread of misinformation, privacy violations, misuse of personal data, cyberbullying, and online fraud. These challenges highlight importance of digital literacy in foster public awareness and promote safe and responsible use of technology. This education aimed to enhance the understanding of residents of Polaman Village regarding safe social media practices, personal data protection, misinformation prevention, and digital fraud awareness. Methods employed included presentations, interactive discussions, case studies, and question-and-answer sessions. Topics covered digital footprints, privacy, personal data protection, cyberbullying, identification of hoaxes, and awareness of fraud schemes involve APK files and suspicious links. Activity was conducted face-to-face and involved community members and village officials as participants. The results indicated an improvement in participants understanding of the importance of protected personal data, identify reliable information, and adopt responsible behavior in digital environments. Participant enthusiasm during discussions also demonstrated that materials presented were highly relevant to current community needs. Therefore, this program successfully increased public awareness of the challenges and risks associated with the digital era.